1988
DOI: 10.1159/000185077
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Left-Ventricular Changes Associated with Chronic Hemodialysis

Abstract: To assess the reasons for the frequent cardiovascular complications in patients with end-stage renal disease (ESRD), 61 out of 131 normotensive ESRD patients originally examined (mean ESRD duration: 71 ± 41 months) were followed over 2.5 years by echo-, electro- and mechanocardiography. Clinical and biochemical parameters were comparable. The prevalence of pericardial effusion (3%), pericardial thickening (14%), aortic valve sclerosis (14%) and mitral valve anulus sclerosis (12%) was unchanged. The interventri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
63
1
1

Year Published

1991
1991
2014
2014

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(71 citation statements)
references
References 24 publications
(33 reference statements)
6
63
1
1
Order By: Relevance
“…39 Importantly, left ventricular growth is modifiable through treatment of hypertension and anaemia. 40 LVH rose proportionally to GFR decline reaching a value >50% in stage V. In the present study, we found LVH in 44.4% of patients in stage V by echocardiography and a slightly lower percentage (40.7%) by ECG. Our study also shows that, LVH increased proportionally from stage III-V with a statistically significant difference.…”
Section: Discussionsupporting
confidence: 49%
“…39 Importantly, left ventricular growth is modifiable through treatment of hypertension and anaemia. 40 LVH rose proportionally to GFR decline reaching a value >50% in stage V. In the present study, we found LVH in 44.4% of patients in stage V by echocardiography and a slightly lower percentage (40.7%) by ECG. Our study also shows that, LVH increased proportionally from stage III-V with a statistically significant difference.…”
Section: Discussionsupporting
confidence: 49%
“…LVH in uremic patients is correlated with the BP, but is not completely explained by a high BP [22]. Even in HD patients with a normal predialysis BP, Hüting et al [23]documented an increase of the LV mass over 2 years despite the absence of hypertension. Using multivariate analysis, Harnett et al [24]showed that other factors such as chronic HD, age, and systolic BP were independent risk factors for LVH.…”
Section: Risk Factorsmentioning
confidence: 99%
“…The slight hypertrophy of the left ventricular wall which was recorded is probably an effect of longstanding hypertension and periods of fluid overload prior to the renal transplantation (Thuesen et al 1988;Htiting et al 1988;Sampson et al 1990). In spite of this almost inevitable experience in this disease, left ventricular systolic function was well preserved in all patients.…”
Section: Discussionmentioning
confidence: 96%